Al-Musykilāt wa Challuhā fī Tathbīqi Istirātījiyyati Ta’limi al-Lughah al-‘Arabiyyah ‘alā Asāsi at-Ta’allumi al-Iliktarūnī li Badri al-Khan bi Madrasati al-Qānitati al-Ibtidā`iyyati al-Islāmiyyati Palangkaraya - Fitriana, Yulia Maulidina; Shobri, Yus Arija; Hidayat, M. Syaiful Bahri; Fadhili, Ahmad Fajri (Universitas Negeri Malang, 2024)
E-learning means using information technology with computers or smart tools that are interconnected between students and teachers so that the learning process continues to be implemented correctly through technology, especially during the Covid-19 pandemic. However, it is undeniable that schools often face problems in their implementation. As in the Al-Qonita Islamic Elementary School, this research aims to reveal and solve problems in applying the Arabic language teaching strategy based on e-learning by Badr Al-Khan in the Al-Qonita Islamic Elementary School Palangka Raya. In writing this research, the researcher used the qualitative approach with the type of case study. Furthermore, use the data collection method of interview, observation, documentation, and questionnaire. The researcher used the method of analyzing the data for the model of Miles and Huberman. The results of this study revealed that Al-Qonita Islamic Elementary School Palangka Raya has problems in applying the strategy of teaching the Arabic language based on e-learning by Badr Al-Khan, meaning a problem in presenting the learning process on e-learning, student participation in learning, and the use of applications. The school provides the ability to solve problems such as designing learning steps on e-learning, communicating with students intensively, and providing training on using applications.التعلم الإلكتروني يعني استخدام تكنولوجيا المعلومات باستخدام أجهزة الكمبيوتر أو الأدوات الذكية المترابطة بين الطلاب والمعلمين بحيث استمرّ تنفيذ عملية التعلم بشكل صحيح من خلال استخدام التكنولوجيا خصوصا أثناء جائحة كوفيد -19. ومع ذلك، غير ممكن إنكار أنه غالبًا تواجه المدارس مشاكل في تنفيذها. كما هو الحال في مدرسة القانتة، و أهدف هذ البحث لكشف المشكلات وحلها في تطبيق استراتيجية تعليم اللغة العربية على أساس التعلم الإلكتروني لبدر الخان في مدرسة القانتة الإبتدائية الإسلامية فالانكارايا. استخدمت الباحثة في كتابة هذا البحث بالمدخل الكيف بنوع الدراسة الحالة. واستخدم طريقة جمع البيانات نحو طريقة المقابلة والملاحظة والتوثيق والاستبانة. واستخدمت الباحثة طريقة تحليل البيانات في هذه البحث لنموذج ميلس وهوبرمان. ونتائج هذه الدراسة اكتشفت انها المدرسة القانتة الإبتدائية الإسلامية فالانكارايا لها مشكلات في تطبيق استراتيجية تعليم اللغة العربية على أساس التعلم الإلكتروني لبدر الخان، يعني مشكلة في تقديم عملية التعلم على التعلم الإلكتروني، والمشاركة الطلاب في التعلم، واستخدام التطبيقات. توفير المدرسة القانتة حل المشكلة مثل وتصميم خطوات التعلم على التعلم الإلكتروني، والتواصل مع الطلاب بشكل مكثف، وتوفير التدريب على استخدام التطبيقات.